If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2 = 4 Reorder the terms: -2 + 2x = 4 Solving -2 + 2x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = 4 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 4 + 2 2x = 4 + 2 Combine like terms: 4 + 2 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| (-3)(-5)(-4)(-10)= | | -1=-7x+6y | | y^2+y-0=0 | | x-246=688 | | -8(-4)= | | -7(-7)+6y=-42 | | -32-(-74)= | | 2/3(12x-15)+1/4(24x-16) | | 6k-13=4k+14 | | x/3+5=x/6+18 | | -32-16-(-27)= | | -4(-3a+6)+8(8a+7)=-44 | | 2+3x+5=25 | | 3x+2x+7=22 | | 2z^2+2z+13=0 | | (295.5-y)/5.5=x | | 3(8-7n)=-34+8n | | 295.50-y/5.5=x | | m-3=2 | | -56+38= | | -7*-7+6y=-42 | | 4a-8(-5-6a)=40-8a | | 11+3x-7=9 | | 106=-7(p-7)+1 | | -1=-10/9x+10 | | -1=-10/9+10 | | -16-5x=5-sx | | (4x-3)/5=(2x-7)/8 | | -1.1111=-10/9x+10 | | -1.1111=-10/9+10 | | 82=4x-2(1-4x) | | -10/9*-1.1111+10 |